Model Pembelajaran Gamifikasi dalam Meningkatkan Motivasi Belajar Siswa Melalui Teknologi: Gamification Learning Model to Increase Student Motivation through Technology - Fajar Ayu, Amilia; Puspitasari, Asih; Hidayati, Nurin; Fitra Andikos, Adi (ISEDU : Islamic Education Journal, 2024)
This piece falls under the category of scholarly writing. It is a review of the literature, a type of scientific investigation that focuses on a particular subject. One of the ideas in e-learning is gamification. In the English language, it is frequently called "Gamification." Gamification is the process of using game mechanics and strategies to tackle problems outside of games. A key element in raising the standard of education is student motivation. Technology can be used as a tool to create a more dynamic and engaging learning environment in an effort to increase student motivation. The use of game mechanics and components to improve learning outcomes and motivation is known as "gamification" in education.